دراسة مقارنة بين خياطة الرحم خارج البطن خلال القيصرية مع خياطة الرحم داخل البريتوان أو في الموضع - نعيسة, ثورة (Latakia University Journal -Medical Sciences Series, 2019)
Abstract: The objective of this study is to assess intra operative and post operative advantages and disadvantages following exteriorization of uterus as Compared to those with intraperitoneal or in_situ repair , and to assess intra operative and immediate post operative morbidity following exteriorization of uterus as Compared to in_situ repair. In this randomized controlled prospective study 100 women planned for cesarean were included .The women were randomly assigned to two groups: exteriorization group and in situ group variables analysed were intra operative blood loss intraoperative and immediate post operative nausea and vomiting, post operative pain and post operative analgesic requirement post operative fever morbidity post operative fall in hemoglobin and wound infection. There was significant difference in the intra operative blood loss between the two groups Blood loss being less in exteriorization group Pvalue < 0.0014 . There was significant difference in the operative time,exteriorization required less time as compared to insitu group Pvalue < 0.0001.There was significant difference in perioperative fall in hemoglobin.The fall in haemoglobin was less in exterioration group Pvalue<0.0001 There was no significant difference in the intra operative and opst operative nausea,vomiting , ,post operative pain,post operative analgesic requirement post operative febrile morbidity, and wound infection between the two groups. Uterine exteriorization is avaluable technique in uterine repair in cesarean section interms of better visualization of scar. There was significantly less intr aoperative blood loss and less fall in perioperative haemoglobin in exteriorization group. The operating time was also shorter in exteriorization group. الخلاصة :تهدف الدراسة إلى تقييم الفوائد أو الميزات والسلبيات خلال العمل الجراحي أو بعد العمل الجراحي التي تتلو خياطة الرحم خارجاً مقارنة مع خياطته ضمن البريتوان أو في موضعه ومقارنة المراضة خلال العمل الجراحي أو التي تتلوه مباشرة بين الطريقتين. أجريت هذه الدراسة على 100 مريضة خطط إجراء عمل قيصري لهنّ . وقسمت المريضات إلى مجموعتين : مجموعة 1 : وعددها خمسون :أجريت لهنّ خياطة الرحم خارج البطن مجموعة2 : وعددها خمسون أجريت لهنّ خياطة الرحم ضمن البريتوان أو في الموضع. درس خلال العمل الجراحي النزف والغثيان والإقياء بعد العملية مباشرةً ،تمت دراسة الألم بعد العملية .ا ومسكنات الألم المعطاة كما درست الحمى بعد العمل الجراحي ومقدار نقص الهيموغلوبين ،وإنتان الجرح بعد القيصرية يوجد فرق هام في مقدار فقد الدم بين المجموعتين النزف كان اقل في المجموعة الأولىPvalue<0,0014 وكان هناك فرق هام في مدة العمل الجراحي Pv<0,0001 كما كان هناك فرق هام في معدل نقص خضاب الدم حيث كان نقص خضاب الدم أقل في المجموعة الأولى لا يوجد فرق هام بين المجموعتين فيما يتعلق بالغثيان والإقياء والألم بعد العمل الجراحي وفيما يتعلق بالمسكنات المعطاة وإنتان الجرح بين المجموعتين خياطة الرحم خارجاً هو تكتيك قيم يسمح برؤية جيدة لشق الرحم،ويكون فقر الدم اقل ونقص خضاب الدم أيضاً اقل في المجموعة الأولى وكذلك مدة العمل الجراحي.